Development of Online Environmental Monitoring System with Location Awareness - Dhiren P Mistry; Kiran R Trivedi (Bulletin of Electrical Engineering and Informatics, 2012)
Despite the economic downturn, there have been quite a few new developments in the world of remote measurements lately. This Paper introduced the concept of OEMS where sensors connected to the microcontroller based system and which is the part of enterprises, retail outlets, factories, and warehouse or any remote place. The system sends the data to the Internet where specialized web applications receive the information for processing and display. One of these specialized web applications is Pachube, (http://www.pachube.com) which bills itself as a real-time data brokerage platform. Pachube enables people to tag and share real time sensor data from objects, devices and spaces around the world. The system basically sense the Environmental parameter like temperature, humidity, Carbon Monoxide Level, level of Alcohol Gases, of the Area in which system is located. By using a GPS technology, track the location of the area in terms of latitude and longitude. All the data of Sensors and GPS data uploaded to the Pachube using a GPRS with the help of GSM Modem.